Alarm: Mankind is Not Ready for Inevitable Global Climate Change - Krasnyansky, Dr. Mikhail (International Journal of Environment, Agriculture and Biotechnology, 2023)
This article is a scientific review, first, of the consequences of global warming and climate change, and second, of the urgent ways for humanity to adapt to these climate changes. It is shown that an increase in the concentration of CO2 in the atmosphere, as well as an increase in its average temperature, correlates well with an increase in the number of natural disasters and, accordingly, an increase in budget costs for the removal of their consequences. On the other hand, the impossibility of completely stopping global climate change, let alone returning to its 1970 parameters, is discussed, for example: removing billions of tons of CO2 from the Earth's atmosphere; restoring trillions of tons of ice at the poles of the Earth and its mountain peaks; reduce the acidity of the waters of the World Ocean and its cooling. Hence the conclusion is made about the inexpediency of spending hundreds of billions of dollars on "the fight against climate change" and the expediency of spending these billions on the urgent adaptation of mankind to an already changed climate. Further, the article examines in detail the ways and options to prevent the destruction and loss caused by hurricanes, flooding, wildfires, massive burning of fossil fuels, traditional agriculture, as well as huge pollution of the World Ocean: replacement of fossil fuels with green energy and green transport, the construction of only hurricane-resistant and fire-resistant buildings in hazardous areas, the construction of dams and powerful drainage systems in areas of probable flooding, the transition to superconducting underground electrical cables, the widespread use of small modular low-enriched uranium nuclear reactors, widespread use of heat pumps, the transition from traditional cattle breeding to artificial meat, the widespread in agriculture use of so-called vertical farms, minimization of food losses at all stages, and more. The main idea of this report was clearly expressed by Charles Darwin in his well-known quote: “It is not the strongest and smartest who survive but the one who adjusts best to the changing environment.” That is, not the strongest nation (with the largest GDP), not the smartest nation (which will learn to extract all the excess CO2 from the atmosphere), but the nation that is best adapted to live in this changed climate (with hurricanes, floods, droughts, wildfires, etc.) - will have more chances to survive